Catecholamine-Based Treatment in AD Patients: Expectations and Delusions - Stefani, Alessandro; Olivola, Enrica; Liguori, Claudio; Hainsworth, Atticus H.; Saviozzi, Valentina; Angileri, Giacoma; D’Angelo, Vincenza; Galati, Salvatore; Pierantozzi, Mariangela (Frontiers in Aging Neuroscience, 2015)
In Alzheimer disease, the gap between excellence of diagnostics and efficacy of therapy is wide. Despite sophisticated imaging and biochemical markers, the efficacy of available therapeutic options is limited. Here we examine the possibility that assessment of endogenous catecholamine levels in cerebrospinal fluid (CSF) may fuel new therapeutic strategies. In reviewing the available literature, we consider the effects of levodopa, monoamine oxidase inhibitors (MAOI), and noradraneline (NE) modulators, showing disparate results. We present a preliminary assessment of CSF concentrations of dopamine (DA) and NE, determined by HPLC, in a small dementia cohort of either Alzheimer’s disease (AD) or frontotemporal dementia (FTD) patients, compared to control subjects. Our data reveal detectable levels of DA, NE in CSF, though we found no significant alterations in the dementia population as a whole. AD patients exhibit a small impairment of the DA axis and a larger increase of NE concentration, likely to represent a compensatory mechanism. While waiting for preventive strategies, a pragmatic approach to AD may re-evaluate catecholamine modulation, possibly stratified to dementia subtypes, as part of the therapeutic armamentarium.